Wnt Signaling Induces Asymmetric Dynamics in the Actomyosin Cortex of the C. elegans Endomesodermal Precursor Cell - Caroti, Francesca; Thiels, Wim; Vanslambrouck, Michiel; Jelier, Rob (Frontiers in Cell and Developmental Biology, 2021)
During asymmetrical division of the endomesodermal precursor cell EMS, a cortical flow arises, and the daughter cells, endodermal precursor E and mesodermal precursor MS, have an enduring difference in the levels of F-actin and non-muscular myosin. Ablation of the cell cortex suggests that these observed differences lead to differences in cortical tension. The higher F-actin and myosin levels in the MS daughter coincide with cell shape changes and relatively lower tension, indicating a soft, actively moving cell, whereas the lower signal in the E daughter cell is associated with higher tension and a more rigid, spherical shape. The cortical flow is under control of the Wnt signaling pathway. Perturbing the pathway removes the asymmetry arising during EMS division and induces subtle defects in the cellular movements at the eight-cell stage. The perturbed cellular movement appears to be associated with an asymmetric distribution of E-cadherin across the EMS cytokinesis groove. ABpl forms a lamellipodium which preferentially adheres to MS by the E-cadherin HMR-1. The HMR-1 asymmetry across the groove is complete just at the moment cytokinesis completes. Perturbing Wnt signaling equalizes the HMR-1 distribution across the lamellipodium. We conclude that Wnt signaling induces a cortical flow during EMS division, which results in a transition in the cortical contractile network for the daughter cells, as well as an asymmetric distribution of E-cadherin.